Pembuatan Bahan Ajar Pada Mata Pelajaran Administrasi Perpajakan Kelas XII Di SMKN 1 Tanjungpinang - Robby Krisyadi; Mariska Ramadana (Universitas Internasional Batam, 2021)
As an important system in education, learning is an interactive space for the building of teacher and student relationships in order to develop self-potential and achieve learning goals. The outbreak of the Coronavirus (COVID-19) in the world, including Indonesia, has made significant changes for all sectors in Indonesia including education. Changes in learning methods from face-to-face to long-distance become a challenge as well as an obstacle to the learning process, not only for teachers but also for students and parents. Therefore, schools need teaching materials that are able to facilitate the distance learning process by making teaching materials. Making digital teaching materials in the form of learning modules is one form of community service. The target of this activity is students majoring in accounting at SMKN 1 Tanjungpinang for the subject of Tax Administration. The output produced from this activity is a learning module equipped with case examples, practice questions, and answer keys. This learning module is expected to make it easier for students during the distance learning process and independent learning and make it easier for teachers to achieve learning goals. It is hoped that this module can continue to be used and developed to support the learning process.